Satisfaction of elderly sisters with activities, facilities and services in the homes for the aged women religious in Metro Manila. - Surapee Philippe Vareevong (1987)
This study evaluated the existing activities, facilities and services offered in 2 homes for elderly sisters, namely the Sisters of St. Paul of Chartres (SPC) Vigil House, Quezon City and St. Catherine Labourre Community of the Daughters of Charity of St. Vincent de Paul, Paranaque. It was hoped that the presence/provision of their activities, facilities and services would: 1) help the elderly sisters attain maximum satisfaction in their golden years and 2) help the administrators of these homes to plan, formulate and implement policies that will maximize the comfort and happiness of the residents. The research methodology used in this study was the descriptive survey, 58 elderly sisters and 2 administrators from the above mentioned homes for the aged women religious were chosen as respondents. The purposive sampling was used in this study, following a set of criteria. The instruments used in this study consisted of the questionnaire, checklists, interview and observation. Quantitative data was derived from the repondents qualitative answer in order to arrive at a satisfaction score for each respondent as well as the categories scores for activities, facilities and services. The statistical tools and measurements selected for this study used were descriptive statistics, 1-way analysis of variance and the pooled T-test. The hypotheses were tested at .05 level of significance. From the study findings, it was concluded that: (1) Socio-demographic variable like educational attainment, type of work/position engaged in prior to retirement and length of stay in the institution except the number of years in religious life did not affect the satisfaction level of the elderly sisters as regards activities, facilities and services offered in the homes for the aged women religious. The number of years in the religious life was found to significantly affect the satisfaction level of the elderly sister. The longer the number of years in religious life, the higher the level of satisfaction. (2) Regardless of different homes, there is no significant difference in the level of satisfaction of the elderly sister respondents with the activities, facilities and services provided in the homes for the aged women religious. (3) In general, elderly sisters are satisfied with the activities, facilities and services offered in the homes for the aged women religious. Implications show the importance of healthy interpersonal relationships, more than just excellent physical facilities. Steps should be taken to improve the relationships or the lines of communication between and among the staff and the residents and more important, among the residents themselves.
Thesis (Master of Arts in Nursing)--University of the Philippines Manila.
Keywords: Old age homes; Aged. -- institutional care; Nursing homes